Laparoscopic uteroneovaginal anastomosis in Mayer-Rokitansky Kuster-Hauser syndrome with functioning horns: a case report - Chatterjee, Polly; Bhadra, Avishek; Chatterjee, Abhinibesh; Biswas, Rumela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is characterized by congenital absence of the upper two-thirds of the vagina and a rudimentary or absent uterus, resulting in primary amenorrhea while maintaining normal secondary sexual characteristics. This condition arises from the agenesis or hypoplasia of the mullerian ducts and has an incidence of 1 in 4,000 to 5,000 female births. While most patients possess a non-functioning rudimentary uterus, a minority have functioning endometrium, often leading to complications such as pelvic pain due to hematometra or endometriosis. Surgical interventions typically involve the excision of rudimentary uterine structures, which may relieve pain but eliminate menstruation and the potential for pregnancy. This case details a novel two-stage laparoscopic technique to restore utero-vaginal continuity, thereby enabling menstruation and potential future pregnancies. A 28-year-old woman with MRKH syndrome presented with cyclic abdominal pain since adolescence. Imaging revealed bilateral rudimentary uterine structures with functioning endometrium. A two-stage laparoscopic procedure was performed: initially creating a neovagina and anastomosing the uterine components, followed by re-anastomosis and placement of a copper T multiload 375. The patient experienced her first menstruation 20 days post second surgery, achieving regular cycles thereafter. Follow-up ultrasounds confirmed normal uterine morphology and endometrial thickness. This case underscores the importance of a holistic management approach for MRKH syndrome, and introducing innovative surgical techniques. Our reproducible laparoscopic procedure demonstrates promising outcomes for restoring menstrual function and reproductive potential in patients with a functioning endometrium.